Childfree in the perspective of Manhaj Tarjih Muhammadiyah: An analytic study of childfree with bayani, burhani, and irfani approaches - Putri, Khulanah Sutarno; Daib Insan Labib, Muhammad Alfreda (Universitas Islam Negeri Ar-Raniry, 2024)
The decision not to have children (also known as childfree) is a Western lifestyle that is currently being debated. The concept is regarded as unnatural, contrary to human nature, and outside of the values held by society, particularly Indonesian. From an Islamic perspective, the concept of childfree opposes the shari'ah's goals (maqasid al syari’ah) namely hifzu an-nasl (protecting of offspring). This study focused on discussing about the concept of childfree based on the perspective of Manhaj Tarjih Muhammadiyah. Three basic questions discussed were 1) the history and background of the concept of childfree, 2) the perspective of the Muhammadiyah Tarjih and Tajdid Council and 3) the concept of childfree in the perspective of Manhaj Tarjih Muhammadiyah? The method used in this research is a qualitative method using library research through several primary sources such as the book